Foreign Language Training to Stimulate Cognitive Functions - Sol Herrera Naranjo; Mercedes Suárez de la Torre; Francia Restrepo de Mejía; David Facal (Brain Sciences, 2021)
Adult development throughout a lifetime implies a series of changes in systems, including cognitive and linguistic functioning. The aim of this article is to study the effect of foreign language training on linguistic processing, particularly the frequency of the tip-of-the-tongue (TOT) phenomenon and on other cognitive processes such as processing speed and working memory in adults aged 40 to 60 years. Sixty-six healthy Colombian teachers were enrolled in this study. They were then randomly divided into an experimental group (33 healthy adults who underwent a four-week training period) and a passive control group (33 healthy adults who did not undergo any training). All participants performed induction tasks for the TOT phenomenon, working memory and processing speed before and after the four weeks. Results showed more of an effect in the semantic access, phonological access and processing speed measures with a better performance in the experimental group than in the control group. In Colombia, this type of training is still new and little is known to date about programs to prevent cognitive impairments. The need to conduct more studies confirming or refuting these findings is discussed, thus raising awareness about the extent of this type of training to increase the linguistic and cognitive performance of adults.